PENINGKATAN KEMAMPUAN MENYIMAK ANAK USIA 5-6 TAHUN MELALUI MEDIA POSTER DI TK BAITULLAH PALEMBANG - Hermawati, Revalina; Sri Sumarni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The low ability of early childhood to absorb oral information is the main challenge behind this research. The focus of the study is to improve the listening skills of Group B students of Baitullah Kindergarten Palembang through the integration of systematic visual media. Using the Classroom Action Research (CAR) design model of Kemmis and McTaggart, this study involved 10 students. Data were collected through structured observation and documentation, then analyzed descriptively qualitatively-quantitatively. The results showed a significant transformation: the average listening ability of children increased from a low initial condition to 54.94% in Cycle I, and reached an optimal peak of 85.8% in Cycle II. These findings prove that contextual visual media is effective in creating a conducive learning environment, while accelerating children's receptive abilities in processing instructions and messages continuously.